2022
DOI: 10.3389/fimmu.2022.842669
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Donor and Dietary Fiber Intervention Collectively Contribute to Gut Health in a Mouse Model

Abstract: Transforming the gut microbiota has turned into the most intriguing target for interventions in multiple gastrointestinal and non-gastrointestinal disorders. Fecal microbiota transplantation (FMT) is a therapeutic tool that administers feces collected from healthy donors into patients to help replenish the gut microbial balance. Considering the random donor selection, to maintain the optimal microbial ecosystem, post-FMT is critical for therapy outcomes but challenging. Aiming to study the interventions of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Fecal microbiota transplantation (FMT) has been widely utilized in researches involving animal models ( Daniel et al, 2022 ; Zhong et al, 2022 ). We also performed FMT on MCD rat model to explore the therapeutic or aggravative effects of gut microbiota.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) has been widely utilized in researches involving animal models ( Daniel et al, 2022 ; Zhong et al, 2022 ). We also performed FMT on MCD rat model to explore the therapeutic or aggravative effects of gut microbiota.…”
Section: Methodsmentioning
confidence: 99%
“…The SCFAs including the acetate, propionate, isobutyrate, butyrate, isovalerate, and valerate in cecum digesta were quantified by gas chromatography [22]. In brief, 0.5 g of cecal contents was taken into the centrifuge tube, combined with ddH 2 O, and centrifuged.…”
Section: Short-chain Fatty Acid (Scfa) Analysismentioning
confidence: 99%
“…Studies have demonstrated that both microbes and phages can affect the tight junction protein between intestinal epithelial cells and regulate intestinal permeability under pathological conditions ( Zhong et al, 2022 ). However, it remains unclear the effect of transplantation from 28-day-old AA broiler cecum microorganisms into healthy broiler chickens on the jejunal barrier function, digestion and absorption.…”
Section: Introductionmentioning
confidence: 99%